Studi Evaluasi Usia Fatik Sisa dan Lendutan pada Jembatan Soekarno-Hatta di Kota Malang - Sugeng Prayitno Budio; Agoes Suharjono M. D.; Adi Wijaya (Rekayasa Sipil, 2010)
Bridge is a kind of structure that accept cyclic load because of the traffic load. The cyclic load that continuous day by day could be the cause of collapse. It could happen even all of the strength parameter on the bridge material and structure not over the safety yield stress. This phenomenon called fatigue. The purpose of this study is evaluating of the remaining fatigue life conducted to anticipate damage. While, the deflection of the bridge could be use to measure the serviceability of the bridge. The remaining fatigue life analysis conducted by observe stress range of the bridge that happen while traffic pass the bridge. This stress data then combined with traffic’s volume to get the remaining fatigue life. While, deflection could be found by experiment in the bridge. From the calculation and experiment, known that the reaming fatigue life is different for each span. It could happen because the difference of material, dimension, and truss system in each bridge produce different stress for the same loading case. After calculation we got the result that fatigue life for 40 meter span will end after 36,739 years, and for the 60 meters span the fatigue life already end 12,596 years since it built. And the deflection for 40 meter span is 4 mm and 14 mm for 60 meter span. Both still far from the initiate deflection which is 40 mm and 60 mm. Therefore we can make a conclusion that the bridge still good condition of serviceability.